Análisis de multas e interés por declaraciones tardías y su incidencia en la liquidez - Zambrano Sanchez, Gabriela Michelle (2015)
The proposal to apply it is to conduct a management model oriented Tax compliance officers of the company Sociedad de Hecho cousins is intended to provide the manager of the company regulations and sanctions policies that promote and ensure compliance tax obligations within the set time, thus avoiding the payment of penalties and interest for late declarations, can that money be used in other productive activities for the company to generate future revenues of these activities may be ongoing training aimed at administrative staff tax issues; for the development of this research it has used the technique of the interview and observation to collect the financial and tax information needed to efficiently develop this project integrator. In implementing the proposal an implementation schedule in which it is determined that time each activity will take place in order that the end was established and is, the proposal it is properly established and is easily applied in the company, resources logistic material and the training to make are detailed, so that the manager to review the proposal to determine if it has the financial resources to implement it. It is necessary that managers or directors of companies to establish ongoing programs of tax training to prevent ignorance tax returns made shall be the time set by the tax administration as a result giving the fines and tax interests affecting Liquidity Company.